Risk factors for knee injury in golf: A systematic review - Baker, M. L.; Epari, D. R.; Lorenzetti, S.; Sayers, M.; Boutellier, U.; Taylor, W. R. (Sports Medicine, 2017)
Background: Golf is commonly considered a low-impact sport that carries little risk of injury to the knee and is generally allowed following total knee arthroplasty (TKA). Kinematic and kinetic studies of the golf swing have reported results relevant to the knee, but consensus as to the loads experienced during a swing and how the biomechanics of an individual`s technique may expose the knee to risk of injury is lacking. Objectives: Our objective was to establish (1) the prevalence of knee injury resulting from participation in golf and (2) the risk factors for knee injury from a biomechanical perspective, based on an improved understanding of the internal loading conditions and kinematics that occur in the knee from the time of addressing the ball to the end of the follow-through. Methods: A systematic literature search was conducted to determine the injury rate, kinematic patterns, loading, and muscle activity of the knee during golf. Results: A knee injury prevalence of 3-18% was established among both professional and amateur players, with no clear dependence on skill level or sex; however, older players appear at greater risk of injury. Studies reporting kinematics indicate that the lead knee is exposed to a complex series of motions involving rapid extension and large magnitudes of tibial internal rotation, conditions that may pose risks to the structures of a natural knee or TKA. To date, the loads experienced by the lead knee during a golf swing have been reported inconsistently in the literature. Compressive loads ranging from 100 to 440% bodyweight have been calculated and measured using methods including inverse dynamics analysis and instrumented knee implants. Additionally, the magnitude of loading appears to be independent of the club used. Conclusions: This review is the first to highlight the lack of consensus regarding knee loading during the golf swing and the associated risks of injury. Results from the literature suggest the lead knee is subject to a higher magnitude of stress and more demanding motions than the trail knee. Therefore, recommendations regarding return to golf following knee injury or surgical intervention should carefully consider the laterality of the injury.